PENGARUH HARGA DAN KUALITAS PELAYANAN SERTA KUALITAS PRODUK TERHADAP MINAT PEMBELIAN ULANG DAN KEPUASAN PELANGGAN ONLINE SHOPPING PADA MAHASISWA UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Sari, Rini Kartika; Yulisetiarini, Diah; Sudaryanto, Sudaryanto (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract : This study aimed to analyze the significant influence of price, quality of service and quality of product to repeat purchases interest and customer satisfaction online shopping at University students Abdurachman Saleh Situbondo. This study uses a sample of consumers online shopping are students at the University Abdurachman Saleh Situbondo, sampling method used purposive sampling with the number of respondents is 184 people. Mechanical analysis using SEM. The results showed the quality of price and service quality significantly influence the buying interest, quality of service and product quality significantly influence customer satisfaction and product quality did not significantly affect the interest in the purchase, and the price does not significantly influence customer satisfaction online shopping. Keywords: Interests repeat purchases, customer satisfaction, pricing, quality of service, product quality